POLLEN, PHYTOLITH, STARCH, PROTEIN RESIDUE (CIEP), AND ORGANIC RESIDUE (FTIR) ANALYSIS OF TOOLS FROM SAOYÚ ÆEHDACHO NATIONAL HISTORIC SITE, NORTHWEST TERRITORIES, CANADA - Cummings, Linda Scott; Clark, Caitlin A. (2018)
The Saoyú Æehdacho National Historic Site is located on the southwest shore of Great Bear Lake, Northwest Territories, Canada. Two lithic artifacts were recovered from the surface of a gravel glacial beach ridge along the west shore of the Saoyú (Grizzly Bear Mountain) peninsula. The Archaeology and History Branch of Parks Canada submitted the tools to PaleoResearch Institute for microscopic (pollen, phytolith, starch), protein residue, and Fourier Transform Infrared Spectroscopy (FTIR) analyses to determine how the tools might have been used (Donalee Deck, personal communication, October 23, 2018).